Method for preparing glycolide by catalyzing methyl glycolate with metal-based ionic liquid

By catalyzing the preparation of glycolide by using metal-based ionic liquids, the problems of low catalytic efficiency and high production costs in the prior art are solved, and efficient and low-cost preparation of glycolide is achieved.

CN119823090APending Publication Date: 2025-04-15ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510033148.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, the preparation of glycolide has problems such as low catalytic efficiency, easy pyrolysis of oligoglycolic acid, high glycolide generation temperature and low yield, resulting in a high production cost of high molecular weight polyglycolic acid.

Method used

Using metal-based ionic liquid as a catalyst, low molecular weight polyglycolic acid is obtained by prepolymerization, normal compression polyglycolic acid, linear decompression and vacuum polycondensation reaction with methyl glycolate, and glycolide is obtained through cleavage and cyclization reaction.

Benefits of technology

The yield and purity of glycolide are improved, the synthesis temperature is reduced, the process flow is simplified, and the production cost is greatly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005234738680000111
    Figure BDA0005234738680000111
  • Figure BDA0005234738680000121
    Figure BDA0005234738680000121
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer synthesis, and provides a method for preparing glycolide by catalyzing methyl glycolate with metal-based ionic liquid. The method comprises the following steps: mixing methyl glycolate and a metal-based ionic liquid, sequentially carrying out prepolymerization, normal-pressure polycondensation, linear pressure reduction and vacuum polycondensation, and carrying out a cracking cyclization reaction on obtained low-molecular-weight polyglycolic acid to obtain glycolide, the metal-based ionic liquid is obtained by complexing imidazole type ionic liquid or quaternary phosphonium type ionic liquid and metal halide. The metal-based ionic liquid catalyst provided by the invention has double active sites of zwitterions, not only can activate carbonyl oxygen of a substrate, but also can increase the electronegativity of hydroxyl in the substrate, improve the nucleophilicity of the substrate, reduce the synthesis temperature of a target product glycolide, improve the yield of the glycolide and realize mild and efficient preparation; and by using the metal-based ionic liquid catalyst, the generation of byproducts in the cracking cyclization reaction is effectively inhibited, and the purity of glycolide is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer synthesis, and in particular to a method for preparing glycolide by catalyzing methyl glycolate with metal-based ionic liquid. Background Art

[0002] Polyglycolic acid (PGA) is a widely used fully biodegradable material. At present, the preparation process of PGA mainly adopts the glycolide ring-opening polymerization method, that is, glycolic acid / methyl glycolate is used as raw material to prepare oligomeric PGA, then the oligomeric PGA is cracked and cyclized to generate crude glycolide, which is purified and then ring-opened to obtain high molecular weight PGA. As the core monomer for synthesizing high molecular weight PGA, the highly selective preparation of glycolide has become a bottleneck restricting the industrial production of PGA.

[0003] At present, stannous chloride is a commonly used catalyst for industrial catalysis of oligomeric PGA cracking and cyclization to glycolide. However, due to its single active site, there are two key problems that need to be solved in this process: the first problem is the severe thermal decomposition of oligomeric PGA under reaction conditions. Glycolide is obtained under high temperature and high vacuum (≥260°C, ≤1kPa) reaction conditions. Since the reaction temperature is higher than the thermal decomposition temperature of oligomeric PGA (~240°C), a part of oligomeric PGA will undergo thermal degradation reaction (loss ~20wt%), which will reduce the yield of glycolide and generate a large amount of coke to block the reaction pipeline. The second problem stems from the repolymerization of oligomeric PGA during the reaction process. While oligomeric PGA is cracked and cyclized to glycolide, polymerization reaction will also occur to generate PGA with a larger molecular weight, resulting in an increase in the viscosity of the system, making it difficult to evaporate the generated glycolide, inhibiting the equilibrium from proceeding in the direction of glycolide generation, and reducing the yield of glycolide. Therefore, the yield of glycolide prepared using stannous chloride as a catalyst is low, which will significantly increase the preparation cost of high molecular weight PGA.

[0004] In view of the above problems, patent CN115819395A discloses a method for preparing glycolide using an organic boron catalyst, using an aqueous solution of glycolic acid as a raw material, first dehydrating to obtain oligomeric PGA, and then depolymerizing it to obtain glycolide. The empty p orbital contained in the boron atom in the organic boron catalyst can accept the lone pair of electrons of the carbonyl oxygen in the oligomeric PGA, promote the generation of carbon cations, and thus attack the terminal hydroxyl oxygen of the oligomeric PGA; at the same time, the halogen ions in the organic boron catalyst have strong nucleophilicity and can dynamically shuttle between the electron-deficient boron atom center and the positron nitrogen ion, making it have high catalytic activity, and the obtained glycolide has a purity of 95.5-97.5% and a yield of 90.2-97.2%. However, the preparation method of the organic boron catalyst is extremely complicated and not suitable for large-scale application. Patent CN106397389B provides a process for the synthesis of all-green glycolide. This method uses cyclic / linear organic guanidine compounds as binary composite catalysts and glycolic acid aqueous solution as raw materials. It first dehydrates to obtain oligomeric PGA, and then depolymerizes it to obtain glycolide, and can obtain glycolide with a yield of more than 98.0%. Organic guanidine catalysts also have the disadvantage of complex preparation conditions. In addition, the synthesis temperature of glycolide in this catalyst system is as high as 280°C, which has certain safety hazards. Patent CN113929885B reports a method of catalyzing the high-temperature cracking and cyclization of oligomeric PGA to glycolide using 4,4'-xylylphenylmethyl carbonium tetrafluoroborate / zinc oxide as a composite catalyst. The Lewis acid and highly stable 4,4'-xylylphenylmethyl carbonium in the catalyst improve the efficiency of glycolide generation. Although this method uses methyl glycolate as raw material, the catalyst preparation includes multiple steps of reactions such as reflux, quenching, separation, rotary evaporation, and precipitation, which brings great difficulties to its industrial application.

[0005] The key to the highly selective synthesis of glycolide lies in the activation of specific carbonyl and hydroxyl groups in oligomeric PGA. Designing new high-efficiency catalysts is an effective strategy to solve the problem of thermal decomposition and repolymerization of oligomeric PGA. By enhancing the interaction between the active sites of the catalyst and the oligomeric PGA molecules, the activation energy of the cracking and cyclization reaction is effectively reduced, and the glycolide yield is improved. As a new type of catalyst composed of anions and cations and with a designable structure, ionic liquids have excellent fluidity, high thermal stability, and adjustable acidity. The acidic sites, hydrogen bonds, and ionic microenvironments in ionic liquids can promote the activation of reactants and improve their conversion rate and product selectivity. In addition, compared with glycolic acid, methyl glycolate is a relatively cheap chemical raw material that can be mass-produced.

[0006] Therefore, if an efficient catalyst with a simple preparation process can be developed to catalyze the preparation of glycolide from methyl glycolate, it is expected to greatly reduce the production cost of high molecular weight PGA. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing glycolide by catalyzing methyl glycolate with metal-based ionic liquid in view of the shortcomings of the prior art.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing glycolide by catalyzing methyl glycolate with a metal-based ionic liquid, comprising the following steps:

[0010] 1) methyl glycolate and metal-based ionic liquid are mixed and sequentially subjected to prepolymerization, normal compression polymerization, linear decompression, and vacuum polycondensation to obtain low molecular weight polyglycolic acid;

[0011] 2) low molecular weight polyglycolic acid undergoes cleavage and cyclization reaction to obtain glycolide;

[0012] Methyl glycolate is an intermediate product in the production of ethylene glycol from coal;

[0013] The metal-based ionic liquid is obtained by complexing an ionic liquid with a metal halide, and the ionic liquid is an imidazole-type ionic liquid or a quaternary phosphine-type ionic liquid.

[0014] Preferably, the imidazolium-type ionic liquid in step 1) comprises 1-alkyl-3-methylimidazolium chloride, 1-alkyl-3-methylimidazolium bromide, 1-alkylsulfonic acid-3-methylimidazolium chloride, 1-alkylsulfonic acid-3-methylimidazolium bromide, 1-methylimidazolium hydrochloride or 1-methylimidazolium bromide;

[0015] The quaternary phosphine type ionic liquid comprises tetrabutylphosphonium chloride, tetrabutylphosphonium bromide, dodecyltributylphosphonium chloride, dodecyltributylphosphonium bromide, tetradecyltributylphosphonium chloride, tetradecyltributylphosphonium bromide, hexadecyltributylphosphonium chloride or hexadecyltributylphosphonium bromide;

[0016] The metal halide comprises stannous chloride, stannic chloride, aluminum chloride, zinc chloride, ferric chloride, stannous bromide, stannic bromide, aluminum bromide, zinc bromide or ferric bromide.

[0017] Preferably, the alkyl groups in 1-alkyl-3-methylimidazolium chloride and 1-alkyl-3-methylimidazolium bromide are independently straight-chain alkyl groups of C1-C16, and the alkyl groups in 1-alkylsulfonic acid-3-methylimidazolium chloride and 1-alkylsulfonic acid-3-methylimidazolium bromide are independently straight-chain alkyl groups of C3-C4.

[0018] Preferably, in step 1), the molar ratio of the ionic liquid to the metal halide is 1:0.5-3, the temperature of the complex reaction is 50-100°C, and the time of the complex reaction is 2-12h.

[0019] Preferably, the mass of the metal-based ionic liquid in step 1) is 0.3-0.7% of the mass of methyl glycolate.

[0020] Preferably, the temperature of the prepolymerization in step 1) is 130-160° C., and the time of the prepolymerization is 60-180 min; the temperature of the normal compression polymerization is 160-200° C., and the time of the normal compression polymerization is 30-60 min.

[0021] Preferably, in step 1), the linear decompression to an absolute pressure of 1-5 kPa takes 3-5 h; the absolute pressure of the vacuum polycondensation is 1-5 kPa, and the vacuum polycondensation time is 30-60 min.

[0022] Preferably, the temperature of the cleavage cyclization reaction in step 2) is 240-270° C., the absolute pressure of the cleavage cyclization reaction is 0.6-1 kPa, and the time of the cleavage cyclization reaction is 30-120 min.

[0023] The beneficial effects of the present invention include the following:

[0024] 1) The present invention provides a method for preparing glycolide from methyl glycolate using a green catalytic metal-based ionic liquid, wherein methyl glycolate is used as a raw material and a metal-based ionic liquid formed by a complex of an ionic liquid and a metal halide is used as a catalyst, and methyl glycolate is first catalyzed to be dealcoholized and prepolymerized into oligomeric PGA, and then the oligomeric PGA is catalyzed to be cracked and cyclized into glycolide, so as to solve the problems of low catalytic efficiency of existing traditional catalysts, easy thermal decomposition of oligomeric PGA, high glycolide formation temperature and low yield. The metal-based ionic liquid catalyst used in the present invention not only has a simple synthesis process, is easy to be industrialized and amplified, but also has high catalytic efficiency.

[0025] 2) Compared with traditional metal-based catalysts, such as Lewis acid salts of metal tin and zinc, the metal-based ionic liquid catalyst of the present invention has dual anionic and cationic active sites, which can not only activate the carbonyl oxygen of the substrate, but also increase the electronegativity of the hydroxyl group in the substrate, improve its nucleophilicity, reduce the synthesis temperature of the target product glycolide, improve the yield and purity of glycolide, and achieve its gentle and efficient preparation. The use of metal-based ionic liquid catalysts effectively inhibits the generation of by-products in the cracking cyclization reaction, improves the purity of glycolide, and is conducive to the subsequent purification of glycolide. Metal-based ionic liquids are homogeneous catalysts in the synthesis of glycolide. Good solubility increases the activity of molecules in the entire reaction system, increases the collision probability between substrate molecules, and improves the yield of glycolide. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing glycolide by catalyzing methyl glycolate with a metal-based ionic liquid, comprising the following steps:

[0027] 1) After methyl glycolate and metal-based ionic liquid are mixed, prepolymerization, normal compression polymerization, linear decompression, and vacuum polycondensation are sequentially performed to obtain low molecular weight polyglycolic acid (oligomeric PGA);

[0028] 2) low molecular weight polyglycolic acid undergoes cleavage and cyclization reaction to obtain glycolide;

[0029] Methyl glycolate is an intermediate product in the production of ethylene glycol from coal;

[0030] The metal-based ionic liquid is obtained by complexing an ionic liquid with a metal halide, and the ionic liquid is an imidazole-type ionic liquid or a quaternary phosphine-type ionic liquid.

[0031] In the present invention, the imidazolium-type ionic liquid in step 1) preferably comprises 1-alkyl-3-methylimidazolium chloride, 1-alkyl-3-methylimidazolium bromide, 1-alkylsulfonic acid-3-methylimidazolium chloride, 1-alkylsulfonic acid-3-methylimidazolium bromide, 1-methylimidazolium hydrochloride or 1-methylimidazolium bromide;

[0032] The quaternary phosphine ionic liquid preferably comprises tetrabutylphosphonium chloride, tetrabutylphosphonium bromide, dodecyltributylphosphonium chloride, dodecyltributylphosphonium bromide, tetradecyltributylphosphonium chloride, tetradecyltributylphosphonium bromide, hexadecyltributylphosphonium chloride or hexadecyltributylphosphonium bromide;

[0033] The metal halide preferably comprises stannous chloride, stannic chloride, aluminum chloride, zinc chloride, ferric chloride, stannous bromide, stannic bromide, aluminum bromide, zinc bromide or ferric bromide.

[0034] In the present invention, the alkyl group in 1-alkyl-3-methylimidazolium chloride and 1-alkyl-3-methylimidazolium bromide is independently preferably a straight-chain alkyl group of C1-C16, more preferably a straight-chain alkyl group of C2-C8, and more preferably a straight-chain alkyl group of C2-C4; the alkyl group in 1-alkylsulfonic acid-3-methylimidazolium chloride and 1-alkylsulfonic acid-3-methylimidazolium bromide is independently preferably a straight-chain alkyl group of C3-C4, and more preferably a straight-chain alkyl group of C4.

[0035] In the present invention, the metal-based ionic liquid preferably comprises 1-ethyl-3-methylimidazolium stannous chloride, 1-butyl-3-methylimidazolium stannous chloride, 1-octyl-3-methylimidazolium stannous chloride, 1-dodecyl-3-methylimidazolium stannous chloride, 1-hexadecyl-3-methylimidazolium stannous chloride, 1-butyl-3-methylimidazolium stannous chloride, 1-butyl-3-methylimidazolium aluminum chloride, 1-butyl-3-methylimidazolium zinc chloride, 1-butyl- One or more of 3-methylimidazole zinc bromide, 1-butyl-3-methylimidazole stannous bromide, 1-propylsulfonic acid-3-methylimidazole stannous chloride, 1-butylsulfonic acid-3-methylimidazole stannous chloride, 1-butylsulfonic acid-3-methylimidazole stannous chloride, 1-methylimidazole stannous chloride, tetrabutylphosphine chloride-stannous chloride, tetrabutylphosphine chloride-stannous chloride, tetrabutylphosphine chloride-aluminum chloride, tetrabutylphosphine chloride-zinc chloride and tetrabutylphosphine bromide-stannous bromide.

[0036] In the present invention, the molar ratio of the ionic liquid to the metal halide in step 1) is preferably 1:0.5-3, more preferably 1:1-2.5, and more preferably 1:1.5-2; the temperature of the complex reaction is preferably 50-100°C, more preferably 60-90°C, and more preferably 70-80°C; the time of the complex reaction is preferably 2-12h, more preferably 4-10h, and more preferably 5-8h.

[0037] In the present invention, the complexation reaction is preferably carried out under stirring conditions.

[0038] In the present invention, the mass of the metal-based ionic liquid in step 1) is preferably 0.3-0.7% of the mass of methyl glycolate, more preferably 0.4-0.6%, and more preferably 0.5%.

[0039] In the present invention, the temperature of the prepolymerization in step 1) is preferably 130-160°C, more preferably 140-150°C, more preferably 145°C, and the time of the prepolymerization is preferably 60-180min, more preferably 70-120min, more preferably 80-100min; the prepolymerization is dealcoholization prepolymerization; the temperature of the normal compression polymerization is preferably 160-200°C, more preferably 170-190°C, more preferably 180°C, and the time of the normal compression polymerization is preferably 30-60min, more preferably 40-50min, more preferably 45min.

[0040] In the present invention, the linear decompression in step 1) is preferably to an absolute pressure of 1 to 5 kPa, more preferably 2 to 4 kPa, more preferably 3 kPa, and the time for linear decompression from normal pressure to 1 to 5 kPa is preferably 3 to 5 h, more preferably 3.5 to 4.5 h, more preferably 4 h; the absolute pressure of the vacuum polycondensation is preferably 1 to 5 kPa, more preferably 2 to 4 kPa, more preferably 3 kPa, and the time for vacuum polycondensation is preferably 30 to 60 min, more preferably 35 to 55 min, more preferably 40 to 50 min.

[0041] In the present invention, the low molecular weight polyglycolic acid is pulverized and vacuum dried in sequence before undergoing a cleavage cyclization reaction; the vacuum drying temperature is preferably 160-180°C, more preferably 165-175°C, and more preferably 170°C.

[0042] In the present invention, the temperature of the cleavage cyclization reaction in step 2) is preferably 240-270°C, more preferably 250-260°C, and more preferably 255°C. The absolute pressure of the cleavage cyclization reaction is preferably 0.6-1 kPa, more preferably 0.7-0.9 kPa, and more preferably 0.8 kPa. The time of the cleavage cyclization reaction is preferably 30-120 min, more preferably 50-100 min, and more preferably 60-80 min.

[0043] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] In the examples, the weight average molecular weight (M) of oligomeric PGA was determined using gel permeation chromatography (GPC). w ), the purity of glycolide was determined by gas chromatography; the reaction bottle with a side tube glass stopper was purchased from Shanghai Titan Technology Co., Ltd.;

[0045] Methyl glycolate is an intermediate product of coal-to-ethylene glycol production; metal-based ionic liquids are obtained by complexing ionic liquids with metal halides at 80°C for 8 hours.

[0046] Example 1

[0047] 20g of methyl glycolate and 0.1g of 1-ethyl-3-methylimidazolium stannous chloride (obtained by complexing 1-ethyl-3-methylimidazolium chloride with stannous chloride at a molar ratio of 1:2) were added to a 100mL glass slug reaction bottle with a side tube, and the air and water in the reaction bottle were purged with nitrogen. The temperature was raised to 150°C in an oil bath, and prepolymerized at 150°C for 120min, then raised to 170°C, and normal compression polymerization was performed at 170°C for 30min. Then, the absolute pressure of the reaction system was linearly reduced from normal pressure to 3kPa within 4.5h, and vacuum polycondensed at 3kPa and 170°C for 30min to obtain 11.79g of solid product oligomeric PGA, with a yield of 91.5% and a weight average molecular weight of 9623Da. The obtained oligomeric PGA was crushed and vacuum dried at 170°C by pumping to a vacuum degree of -0.1 MPa to remove unreacted methyl glycolate and other low-boiling impurities.

[0048] Add 5 g of dried oligomeric PGA to a 100 mL round-bottom flask, slowly evacuate the reaction system to an absolute pressure of 1 kPa, control the condenser temperature at 80 °C to ensure that the generated glycolide flows smoothly into the collection bottle, raise the temperature to 250 °C in an oil bath, and perform cracking and cyclization at 250 °C for 60 min to collect 4.33 g of light yellow glycolide with a yield of 86.6% and a purity of 91.0%.

[0049] Example 2

[0050] The metal-based ionic liquid is 1-butyl-3-methylimidazolium stannous chloride (obtained by complexing 1-butyl-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:2), and the other reaction conditions are the same as those in Example 1. In this example, 11.80 g of solid product oligomeric PGA is obtained with a yield of 91.6% and a weight-average molecular weight of 9703 Da. 4.36 g of light yellow glycolide is collected with a yield of 87.2% and a purity of 91.1%.

[0051] Example 3

[0052] The metal-based ionic liquid is 1-octyl-3-methylimidazolium stannous chloride (obtained by complexing 1-octyl-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:2), and the other reaction conditions are the same as those in Example 1. In this example, 11.92 g of solid product oligomeric PGA is obtained with a yield of 92.6% and a weight-average molecular weight of 8927 Da. 4.10 g of light yellow glycolide is collected with a yield of 82.0% and a purity of 92.3%.

[0053] Example 4

[0054] The metal-based ionic liquid is 1-dodecyl-3-methylimidazolium stannous chloride (obtained by complexing 1-dodecyl-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:2), and the other reaction conditions are the same as those in Example 1. In this example, 11.82 g of solid product oligomeric PGA is obtained with a yield of 91.8% and a weight-average molecular weight of 8684 Da. 4.12 g of light yellow glycolide is collected with a yield of 82.3% and a purity of 90.8%.

[0055] Example 5

[0056] The metal-based ionic liquid is 1-hexadecyl-3-methylimidazolium stannous chloride (obtained by complexing 1-hexadecyl-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:2), and the other reaction conditions are the same as those in Example 1. In this example, 11.52 g of solid product oligomeric PGA is obtained with a yield of 89.4% and a weight-average molecular weight of 8549 Da. 4.11 g of light yellow glycolide is collected with a yield of 82.1% and a purity of 92.2%.

[0057] Example 6

[0058] 20g of methyl glycolate and 0.06g of 1-butanesulfonic acid-3-methylimidazolium tin chloride (obtained by complexation reaction of 1-butanesulfonic acid-3-methylimidazolium chloride and tin chloride at a molar ratio of 1:2) were added to a 100mL glass stopcock reaction bottle with a side tube, and the air and water in the reaction bottle were purged with nitrogen. The temperature was raised to 160°C in an oil bath, and prepolymerized at 160°C for 60min, then raised to 200°C, and normal compression was performed at 200°C for 30min. Then, the absolute pressure of the reaction system was linearly reduced from normal pressure to 1kPa within 3h, and vacuum polycondensed at 1kPa and 200°C for 30min to obtain 12.04g of solid product oligomeric PGA, with a yield of 93.4% and a weight average molecular weight of 9623Da. The obtained oligomeric PGA was crushed and vacuum dried at 170°C by pumping to a vacuum degree of -0.1 MPa to remove unreacted methyl glycolate and other low-boiling impurities.

[0059] Add 5 g of dried oligomeric PGA to a 100 mL round-bottom flask, slowly evacuate the reaction system to an absolute pressure of 1 kPa, control the condenser temperature at 80 °C to ensure that the generated glycolide flows smoothly into the collection bottle, raise the temperature to 250 °C in an oil bath, and perform cracking and cyclization at 250 °C for 60 min to collect 3.95 g of light yellow glycolide with a yield of 79.0% and a purity of 92.4%.

[0060] Example 7

[0061] The metal-based ionic liquid is 1-propylsulfonic acid-3-methylimidazolium stannous chloride (obtained by complexing 1-propylsulfonic acid-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:2). The other reaction conditions are the same as those in Example 6. In this example, 11.95 g of solid product oligomeric PGA is obtained with a yield of 92.8% and a weight-average molecular weight of 9051 Da. 4.09 g of light yellow glycolide is collected with a yield of 81.8% and a purity of 92.9%.

[0062] Example 8

[0063] 20g of methyl glycolate and 0.1g of 1-butyl-3-methylimidazolium stannous bromide (obtained by complexation reaction of 1-butyl-3-methylimidazolium bromide and stannous bromide at a molar ratio of 1:2) were added to a 100mL glass stopcock reaction bottle with a side tube, and the air and water in the reaction bottle were purged with nitrogen. The temperature was raised to 140°C in an oil bath, and prepolymerized at 140°C for 180min, then raised to 160°C, and compressed at 160°C for 60min. Then, the absolute pressure of the reaction system was linearly reduced from normal pressure to 5kPa within 5h, and vacuum polycondensed at 5kPa and 160°C for 60min to obtain 11.83g of solid product oligomeric PGA, with a yield of 91.9% and a weight average molecular weight of 8564Da. The obtained oligomeric PGA was crushed and vacuum dried at 170°C by pumping to a vacuum degree of -0.095 MPa to remove unreacted methyl glycolate and other low-boiling impurities.

[0064] Add 5 g of dried oligomeric PGA to a 100 mL round-bottom flask, slowly evacuate the reaction system to an absolute pressure of 1 kPa, control the condenser temperature at 80 °C to ensure that the generated glycolide flows smoothly into the collection bottle, raise the temperature to 250 °C in an oil bath, perform cracking and cyclization at 250 °C for 60 min, and collect 4.32 g of light yellow glycolide with a yield of 86.3% and a purity of 90.2%.

[0065] Example 9

[0066] The metal-based ionic liquid is 1-butyl-3-methylimidazolium zinc chloride (obtained by complexing 1-butyl-3-methylimidazolium chloride with zinc chloride in a molar ratio of 1:2), and the other reaction conditions are the same as those in Example 1. In this example, 11.40 g of solid product oligomeric PGA is obtained with a yield of 88.5% and a weight-average molecular weight of 8726 Da. 3.92 g of light yellow glycolide is collected with a yield of 78.4% and a purity of 87.1%.

[0067] Example 10

[0068] The metal-based ionic liquid is 1-butyl-3-methylimidazolium zinc bromide (obtained by complexing 1-butyl-3-methylimidazolium bromide with zinc bromide in a molar ratio of 1:2), and the other reaction conditions are the same as those in Example 1. In this example, 11.26 g of solid product oligomeric PGA is obtained with a yield of 87.4% and a weight-average molecular weight of 8264 Da. 3.92 g of light yellow glycolide is collected with a yield of 76.8% and a purity of 84.5%.

[0069] Embodiment 11

[0070] 20g of methyl glycolate and 0.1g of tetrabutylphosphine chloride-stannous chloride (obtained by complexation reaction of tetrabutylphosphine chloride and stannous chloride at a molar ratio of 1:2) were added to a 100mL glass sluice reaction bottle with a side tube, and the air and water in the reaction bottle were purged with nitrogen. The temperature was raised to 130°C in an oil bath, and prepolymerized at 130°C for 180min, then raised to 180°C, and normal compression polymerization was performed at 180°C for 30min. Then, the absolute pressure of the reaction system was linearly reduced from normal pressure to 3kPa within 4h, and vacuum polycondensed at 3kPa and 180°C for 60min to obtain 11.79g of solid product oligomeric PGA, with a yield of 91.5% and a weight-average molecular weight of 9798Da. The obtained oligomeric PGA was crushed and vacuum dried at 170°C with a water pump until the vacuum degree was -0.096MPa to remove unreacted methyl glycolate and other low-boiling impurities.

[0071] Add 5 g of dried oligomeric PGA to a 100 mL round-bottom flask, slowly evacuate the reaction system to an absolute pressure of 1 kPa, control the condenser temperature at 80 °C to ensure that the generated glycolide flows smoothly into the collection bottle, heat the mixture to 250 °C in an oil bath, perform cracking and cyclization at 250 °C for 60 min, and collect 4.38 g of light yellow glycolide with a yield of 87.8% and a purity of 90.5%.

[0072] Example 12

[0073] The temperature for cleavage and cyclization was 260° C., and other reaction conditions were the same as those in Example 2. In this example, 4.44 g of light yellow glycolide was collected, with a yield of 88.8% and a purity of 90.6%.

[0074] Embodiment 13

[0075] The temperature for cleavage and cyclization was 240° C., and other reaction conditions were the same as those in Example 2. In this example, 3.37 g of light yellow glycolide was collected, with a yield of 67.4% and a purity of 88.7%.

[0076] Embodiment 14

[0077] The metal-based ionic liquid is 1-butyl-3-methylimidazolium stannous chloride (obtained by complexing 1-butyl-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:1.5), and the other reaction conditions are the same as those in Example 2. In this example, 11.52 g of solid product oligomeric PGA is obtained with a yield of 89.3% and a weight-average molecular weight of 9462 Da. 3.98 g of light yellow glycolide is collected with a yield of 79.7% and a purity of 92.0%.

[0078] Embodiment 15

[0079] The metal-based ionic liquid is 1-butyl-3-methylimidazolium stannous chloride (obtained by complexing 1-butyl-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:3), and the other reaction conditions are the same as those in Example 2. In this example, 11.57 g of solid product oligomeric PGA is obtained with a yield of 89.7% and a weight-average molecular weight of 9259 Da. 4.18 g of light yellow glycolide is collected with a yield of 83.5% and a purity of 93.4%.

[0080] Example 16

[0081] The absolute pressure of the cleavage and cyclization in the glycolide synthesis system is 0.6 kPa, and other reaction conditions are the same as those in Example 2. In this example, 4.35 g of light yellow glycolide is collected, with a yield of 87.0% and a purity of 92.4%.

[0082] Embodiment 17

[0083] The absolute pressure of the cleavage and cyclization in the glycolide synthesis system is 0.6 kPa, the temperature of the cleavage and cyclization is 240° C., and the other reaction conditions are the same as those in Example 2. In this example, 4.02 g of light yellow glycolide is collected, with a yield of 80.4% and a purity of 91.8%.

[0084] Embodiment 18

[0085] The amount of metal-based ionic liquid 1-butyl-3-methylimidazolium stannous chloride (obtained by complexing 1-butyl-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:2) was 0.14 g, and the other reaction conditions were the same as those in Example 2. In this example, 4.21 g of light yellow glycolide was collected, with a yield of 84.1% and a purity of 92.3%.

[0086] Embodiment 19

[0087] The amount of metal-based ionic liquid 1-butyl-3-methylimidazolium stannous chloride (obtained by complexing 1-butyl-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:2) was 0.12 g, and the other reaction conditions were the same as those in Example 2. In this example, 4.29 g of light yellow glycolide was collected, with a yield of 85.8% and a purity of 92.7%.

[0088] Embodiment 20

[0089] The amount of metal-based ionic liquid 1-butyl-3-methylimidazolium stannous chloride (obtained by complexing 1-butyl-3-methylimidazolium chloride with stannous chloride in a molar ratio of 1:2) used was 0.08 g, and the other reaction conditions were the same as those in Example 2. In this example, 4.12 g of light yellow glycolide was collected, with a yield of 82.4% and a purity of 93.9%.

[0090] Comparative Example 1

[0091] The catalyst is stannous chloride, the temperature of cracking and cyclization is 260°C, and the other reaction conditions are the same as those in Example 1. This comparative example obtains 11.37g of solid product oligomeric PGA with a yield of 88.3% and a weight-average molecular weight of 9433Da. 4.15g of light yellow glycolide is collected with a yield of 83.0% and a purity of 85.4%.

[0092] Comparative Example 2

[0093] The catalyst was stannous chloride, and other reaction conditions were the same as those in Example 1. This comparative example obtained 11.37 g of solid product oligomeric PGA with a yield of 88.3% and a weight-average molecular weight of 9433 Da. 3.85 g of light yellow glycolide was collected with a yield of 76.9% and a purity of 80.6%.

[0094] Comparative Example 3

[0095] The catalyst is stannous chloride, the temperature of cracking and cyclization is 240°C, and the other reaction conditions are the same as those in Example 1. This comparative example obtains 11.37g of solid product oligomeric PGA with a yield of 88.3% and a weight-average molecular weight of 9433Da. 3.12g of light yellow glycolide is collected with a yield of 62.4% and a purity of 76.3%.

[0096] Comparative Example 4

[0097] The catalyst is 1-butyl-3-methylimidazolium chloride, and the other reaction conditions are the same as those in Example 1. This comparative example obtains 10.64 g of solid product oligomeric PGA with a yield of 82.6% and a weight-average molecular weight of 7528 Da. 3.26 g of light yellow glycolide is collected with a yield of 65.2% and a purity of 64.4%.

[0098] The yield and purity of glycolide collected in the examples and comparative examples are shown in Table 1.

[0099] Table 1 Yield and purity of glycolide collected in Examples and Comparative Examples

[0100]

[0101]

[0102] As shown in Table 1, the examples and the comparative examples, from the perspective of Examples 11 and 12 and Comparative Example 1, at a relatively high reaction temperature (260°C), the catalytic activity of the metal-based ionic liquid catalyst is slightly higher than that of the conventional stannous chloride catalyst. However, after the temperature is reduced to 250°C, compared with the conventional stannous chloride (Comparative Example 2), when the metal-based ionic liquid is used as the catalyst (Example 2), the glycolide yield is increased by 13.4% and the purity is increased by 13.0%, indicating that the metal-based ionic liquid catalyst formed by the complexation of the ionic liquid and the metal halide can effectively reduce the synthesis temperature of glycolide and increase the yield and purity of glycolide. As can be seen from Examples 1 to 5, the different cationic structures in the metal-based ionic liquid have a certain influence on the catalytic performance of the catalyst, and the medium-length alkyl chain is more conducive to the synthesis of glycolide.

[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing glycolide from methyl glycolate using a metal-based ionic liquid as catalyst, characterized in that: The following steps are included: 1) methyl glycolate and metal-based ionic liquid are mixed and sequentially subjected to prepolymerization, normal compression polymerization, linear decompression, and vacuum polycondensation to obtain low molecular weight polyglycolic acid; 2) low molecular weight polyglycolic acid undergoes cleavage and cyclization reaction to obtain glycolide; Methyl glycolate is an intermediate product in the production of ethylene glycol from coal; The metal-based ionic liquid is obtained by complexing an ionic liquid with a metal halide, and the ionic liquid is an imidazole-type ionic liquid or a quaternary phosphine-type ionic liquid.

2. The method according to claim 1, characterized in that: Step 1) the imidazolium-type ionic liquid comprises 1-alkyl-3-methylimidazolium chloride, 1-alkyl-3-methylimidazolium bromide, 1-alkylsulfonic acid-3-methylimidazolium chloride, 1-alkylsulfonic acid-3-methylimidazolium bromide, 1-methylimidazolium hydrochloride or 1-methylimidazolium bromide; The quaternary phosphine type ionic liquid comprises tetrabutylphosphonium chloride, tetrabutylphosphonium bromide, dodecyltributylphosphonium chloride, dodecyltributylphosphonium bromide, tetradecyltributylphosphonium chloride, tetradecyltributylphosphonium bromide, hexadecyltributylphosphonium chloride or hexadecyltributylphosphonium bromide; The metal halide comprises stannous chloride, stannic chloride, aluminum chloride, zinc chloride, ferric chloride, stannous bromide, stannic bromide, aluminum bromide, zinc bromide or ferric bromide.

3. The method according to claim 2, characterized in that The alkyl groups in 1-alkyl-3-methylimidazolium chloride and 1-alkyl-3-methylimidazolium bromide are independently C1-C16 straight-chain alkyl groups, and the alkyl groups in 1-alkylsulfonic acid-3-methylimidazolium chloride and 1-alkylsulfonic acid-3-methylimidazolium bromide are independently C3-C4 straight-chain alkyl groups.

4. The method according to claim 2 or 3, characterized in that: Step 1) The molar ratio of the ionic liquid to the metal halide is 1:0.5-3, the temperature of the complex reaction is 50-100°C, and the time of the complex reaction is 2-12 hours.

5. The method according to claim 4, characterized in that Step 1) The mass of the metal-based ionic liquid is 0.3-0.7% of the mass of methyl glycolate.

6. The method according to claim 5, characterized in that Step 1) The prepolymerization temperature is 130-160°C, and the prepolymerization time is 60-180 min; the normal compression polymerization temperature is 160-200°C, and the normal compression polymerization time is 30-60 min.

7. The method according to claim 6, characterized in that In step 1), the linear pressure reduction is reduced to an absolute pressure of 1 to 5 kPa, and the time for linear pressure reduction from normal pressure to 1 to 5 kPa is 3 to 5 hours; the absolute pressure of vacuum polycondensation is 1 to 5 kPa, and the time for vacuum polycondensation is 30 to 60 minutes.

8. The method according to claim 6 or 7, characterized in that: Step 2) The temperature of the cleavage cyclization reaction is 240-270° C., the absolute pressure of the cleavage cyclization reaction is 0.6-1 kPa, and the time of the cleavage cyclization reaction is 30-120 min.

Citation Information

Patent Citations

  • A process for synthesizing glycolide

    CN106397389B

  • A composite catalyst and its application in the preparation of glycolide

    CN113929885B